Nerve terminal bioenergetics and control of neurotransmitter release - Kilbride, Seán (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2009)
Mitochondrial dysfunction has been shown to develop as part of the aging process and has been implicated in chronic neurodegenerative disorders such as Parkinson’s disease, Alzheimer’s disease, amyotrophic lateral sclerosis and Huntington’s disease. However, the initial aetiology of these disorders remains unclear, and the role of mitochondrial dysfunction in their pathogenesis has yet to be fully elucidated. However, mitochondrial involvement in excitotoxicity and oxidative stress has been postulated in affected brain regions in these disorders.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin